2021
DOI: 10.21203/rs.3.rs-143701/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival Rates and Prognostic Factors of COVID-19 Patients: A Registry-Based Retrospective Cohort Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a contagious disease caused by a newly identified coronavirus. Our knowledge about survival rate and prognostic factors of the disease is not established well. This study proposed to estimate the survival function of COVID-19 in western Iran.Methods: This retrospective cohort study was performed in Hamadan province, western Iran. The study included patients that referred to the provincial hospitals during 7 months period from February 20 to September 20, 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Despite the relatively low level of registered mortality from coronavirus infection, it is necessary to take into account the vulnerability of the elderly population and the long-term effects on their health. In fact, the results of recent studies showed a greater risk of death and a low survival rate among the elderly, males, and those with comorbidities 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively low level of registered mortality from coronavirus infection, it is necessary to take into account the vulnerability of the elderly population and the long-term effects on their health. In fact, the results of recent studies showed a greater risk of death and a low survival rate among the elderly, males, and those with comorbidities 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, with aging, the immune response to infectious agents becomes weaker, especially in the elderly, who are more susceptible to infection at its severe stage. Furthermore, underlying diseases, especially in older people, put them at more risk of developing COVID-19 associated with worse outcomes, such as death (4,14).…”
Section: Discussionmentioning
confidence: 99%
“…The results of recently performed meta-analyses in this regard have shown that underlying diseases, such as diabetes, coronary heart disease, and hypertension are the main prognostic factors of high mortality in patients with COVID-19 (5,6). Some studies conducted in Iran and the United States also confirmed age, gender, and underlying diseases as the main prognostic factors responsible for death risk (4,(7)(8)(9). Another meta-analysis indicated a relationship between tobacco use and high mortality rate among patients with COVID-19 (10).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation